Detection of deuterated hydrocarbon nanoparticles in the whirlpool galaxy, M51 - Draine, Bruce T.; Sandstrom, Karin; Dale, Daniel A.; Smith, J.-D. T.; Chown, Ryan; Donnelly, Grant P.; Duval, Sara E.; Whitcomb, Cory M.; Adamo, Angela; Armus, L.; Berg, Danielle A.; Böker, Torsten; et al. (The astrophysical journal. Part 2, Letters, 2025)
Deuteration of hydrocarbon material, including polycyclic aromatic hydrocarbons (PAHs), has been proposed to account for the low gas-phase abundances of D in the interstellar medium (ISM). JWST spectra of four starforming regions in M51 show an emission feature, with central wavelength ∼4.647 μm and FWHM 0.0265 μm, corresponding to the C-D stretching mode in aliphatic hydrocarbons. The emitting aliphatic material is estimated to have (D/H)aliph. ≈0.17 ± 0.02—a factor of ∼104 enrichment relative to the overall ISM. On ∼50 pc scales, deuteration levels toward four H II regions in M51 are 2-3 times higher than in the Orion Bar photodissociation region (PDR), with implications for the processes responsible for the formation and evolution of hydrocarbon nanoparticles, including PAHs. The deuteration of the aliphatic material is found to anticorrelate with helium ionization in the associated H II, suggesting that harsh far-UV radiation may act to lower the deuteration of aliphatics in PDRs near massive stars. No evidence is found for deuteration of aromatic material, with (D/H)arom.  0.016: deuteration of the aliphatic material exceeds that of the aromatic material by at least a factor of 10. The observed levels of deuteration may account for the depletion of D observed in the Galactic ISM. If so, the 4.65 μm feature may be detectable in absorption.
Gesehen am 03.11.2025